Inhibitory Effect of Aqueous Extract of Stem Bark of Cissus populnea on Ferrous Sulphate- and Sodium Nitroprusside-Induced Oxidative Stress in Rat's Testes In Vitro - Akomolafe, Seun F. (Hindawi Publishing Corporation, 2013)

(untitled)
Cissus populnea are plants associated with a myriad of medicinal uses in different parts of the world and are good sources of carotenoids, triterpenoids, and ascorbic acid. The antioxidant properties and inhibitory effect of water extractible phytochemicals from stem bark of C. populnea on FeSO(4) and sodium nitroprusside- (SNP-) induced lipid peroxidation in rat testes were investigated in vitro. The results revealed that the extract was able to scavenge DPPH radical, chelate Fe(2+) and also had a high reducing power. Furthermore, the incubation of the testes tissue homogenate in the presence of FeSO(4) and SNP, respectively, caused a significant increase in the malondialdehyde (MDA) contents of the testes. However, the aqueous extract of the stem bark of C. populnea caused a significant decrease in the MDA contents of both Fe(2+) (EC(50) = 0.027 mg/mL) and SNP- (EC(50) = 0.22 mg/mL) induced lipid peroxidation in the rat testes homogenates in a dose-dependent manner. The water extractible phytochemicals from C. populnea protect the testes from oxidative stress and this could be attributed to their high antioxidant activity: DPPH-scavenging ability, Fe(2+)-chelating and -reducing power. Therefore, oxidatively stress in testes could be potentially managed/prevented by this plant.